Local scale structural changes of working OFET devices. Issue 4 (20th November 2019) - Grodd, L. S.; Mikayelyan, E.; Dane, T.; Pietsch, U.; Grigorian, S.
Abstract : Spatially resolved microstructural studies of operating P3HT OFET resolved by nanoGIXD. Abstract : We present an in situ nanobeam grazing-incidence X-ray diffraction (nanoGIXD) study of real-sized organic field effect transistors (OFET) under applied voltage. The nano-sized beam allows for spatially resolved monitoring of the structural behavior across the poly(3-hexylthiophene) (P3HT) polymer channel and the interfacial regions of the source and drain gold electrodes before and after the operation cycle. We observe major alterations of the gold contacts, in particular diffusion of Au atoms into the polymer channel and a local reorientation of the recrystallized Au nanocrystallites quantified by Hermans' orientation factors. Therefore, the initially sharp electrode-polymer interfaces are significantly modified as a result of device operation. Our findings demonstrate that nanoGIXD has a high potential to probe functionality and reliability of working organic devices.